Unimpeded permeation of water through biocidal graphene oxide sheets anchored on to 3D porous polyolefinic membranes. Issue 15 (29th March 2016) - Mural, Prasanna Kumar S.; Jain, Shubham; Kumar, Sachin; Madras, Giridhar; Bose, Suryasarathi
Abstract : Unimpeded permeation of water through biocidal graphene oxide sheets immobilized on porous polyolefinic membranes. Abstract : 3D porous membranes were developed by etching one of the phases (here PEO, polyethylene oxide) from melt-mixed PE/PEO binary blends. Herein, we have systematically discussed the development of these membranes using X-ray micro-computed tomography. The 3D tomograms of the extruded strands and hot-pressed samples revealed a clear picture as to how the morphology develops and coarsens over a function of time during post-processing operations like compression molding. The coarsening of PE/PEO blends was traced using X-ray micro-computed tomography and scanning electron microscopy (SEM) of annealed blends at different times. It is now understood from X-ray micro-computed tomography that by the addition of a compatibilizer (here lightly maleated PE), a stable morphology can be visualized in 3D. In order to anchor biocidal graphene oxide sheets onto these 3D porous membranes, the PE membranes were chemically modified with acid/ethylene diamine treatment to anchor the GO sheets which were further confirmed by Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and surface Raman mapping. The transport properties through the membrane clearly reveal unimpeded permeation of water which suggests that anchoring GO on to the membranes does not clog the pores. Antibacterial studies through the direct contact of bacteria with GO anchored PE membranes resulted in 99% of bacterial inactivation. The possible bacterial inactivation through physical disruption of the bacterial cell wall and/or reactive oxygen species (ROS) is discussed herein. Thus this study opens new avenues in designing polyolefin based antibacterial 3D porous membranes for water purification.